2022
DOI: 10.1097/mao.0000000000003671
|View full text |Cite
|
Sign up to set email alerts
|

Speech in Noise With Bilateral Active Bone Conduction Implant for Conductive and Mixed Hearing Loss

Abstract: Objective: To evaluate speech in noise results and subjective benefit in bilateral active bone conduction implant (ABCI) for bilateral mixed hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The main aim of the present study was to investigate the role of BC HA fitting in unilateral pseudo-conductive hearing loss. While bilateral bone-anchored devices may provide additional benefits over unilateral fitting [Janssen et al, 2012;Canale et al, 2022], the notion that UCHL, as simulated in this study, should always be amplified with a BC device remains questionable [Alexander et al, 2020;Hirth et al, 2021].…”
Section: Discussionmentioning
confidence: 86%
“…The main aim of the present study was to investigate the role of BC HA fitting in unilateral pseudo-conductive hearing loss. While bilateral bone-anchored devices may provide additional benefits over unilateral fitting [Janssen et al, 2012;Canale et al, 2022], the notion that UCHL, as simulated in this study, should always be amplified with a BC device remains questionable [Alexander et al, 2020;Hirth et al, 2021].…”
Section: Discussionmentioning
confidence: 86%
“…Recent studies reported speech perception advantages in the binaural fitting of BC devices in bilateral conductive hearing loss 6 , 7 . In particular, some previous works in children showed that, due to the binaural unmasking, the bilateral application of a percutaneous BC implant in symmetric bilateral conductive hearing loss results in better sound localisation and speech perception under noise conditions 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Although in bilateral aural atresia hearing rehabilitation with bone conduction hearing aids is nowadays mandatory with a specific bilateral fitting 10 , in the latest years the necessity to rehabilitate a unilateral deficit has also emerged 11 . Indeed, unilateral hearing loss impacts sound localisation and speech perception in background noise, thus being a non-negligible factor in the hearing and speech evolution of the child 12-14 .…”
Section: Introductionmentioning
confidence: 99%
“…These multiple anomalies can have different clinical consequences, and in particular the hearing loss caused by the aural atresia can have an impact on the communication and learning skills during the development. Although in bilateral aural atresia hearing rehabilitation with bone conduction hearing aids is nowadays mandatory with a specific bilateral fitting 10 , in the latest years the necessity to rehabilitate a unilateral deficit has also emerged 11 . Indeed, unilateral hearing loss impacts sound localisation and speech perception in background noise, thus being a non-negligible factor in the hearing and speech evolution of the child [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%